Solve e^x-6e^-x=1

Multiply everything through by ex   and rearrange so it equals zero
you now have e2x -ex-6=0
It is now similar to a quadratic equation, make the dummy substitution y=ex
y=3 or -2 
x= ln(3) and ln(-2) does not exist 

Answered by Kishwar I. Maths tutor

9746 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How do I use the product rule for differentiation?


Prove that 1 + tan^2 x = sec^2 x


Solve x^2 > |5x - 6|


What's the point of Maths?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences